Strategi Pemanfaatan TikTok untuk Membangun Brand Awareness Brand Fashion Ways.co - Wuri Arianty Syamsi; Nasrul Setianto; Asep Saepuloh; Yani Iriani (ProBisnis : Jurnal Manajemen, 2026)
Indonesian local fashion brands continue to grow by offering affordable products that have quality competitive with imported brands. One of the main strategies to enhance competitiveness is the use of digital marketing through the TikTok platform. This study aims to analyze the digital marketing strategies implemented by Ways.co, a local clothing brand that utilizes TikTok as the main channel for promotion and sales. The research method used is qualitative with a case study approach through in-depth interviews with the marketing team. The research results indicate that TikTok plays a strategic role in building brand awareness while also driving sales, particularly due to its integration with marketplaces such as Tokopedia. The marketing strategy employed includes a combination of organic content in the form of live streaming with special price offers, try-on videos using viral sounds, as well as the implementation of a consistent content publication schedule. Additionally, Ways.co also adopts a paid strategy through the Boost Ads feature, with an allocation of IDR 150,000 for promoting live streaming and IDR 200,000 for video content, which has proven effective in expanding audience reach. Internal data shows that about 80% of sales are generated more from TikTok compared to Shopee, with the main success indicator being the number of traffic views during live sessions. This study concludes that TikTok functions not only as a social media platform but also as an integrated marketing channel capable of effectively combining promotion, consumer interaction, and sales.